Learning Achievement In Terms Of Parental Social Support In Elementary School Students - Wardani, Yogi Kusuma; Khosiyono, Banun Havifah Cahyo; Cahyani, Berliana Henu (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2025)
This research is based on the phenomenon of low learning achievement of grade I elementary school children at SD Negeri Soka. This is thought to be due to the lack of social encouragement given by parents to learners. This study aims to reveal learning achievement in terms of parental social support in elementary school students. The population of this study amounted to 138 people, the sample selected was 19 people with cluster random sampling. This type of research data uses quantitative research with a correlational design. The correlational method is one of the various quantitative research methods used in evaluation. Especially to detect the extent to which variation in a factor is related to variation in one or more other factors based on correlation coefficients. The data collection technique for parental attention uses the questionnaire method. Data on student learning achievement using the documentation method by looking at the summative value of the end of semester II of Pancasila education subjects. After the data is collected, data analysis is then carried out using Pearson's product moment correlation. Hypothesis testing using Pearson's product moment correlation aims to prove that the research hypothesis that has been proposed is accepted or rejected. Data analysis was carried out using computer assistance with the SPSS version 26 program. The results of the person product moment correlation analysis showed that the relationship between parental social support and learning achievement of Grade I students of SD Negeri Soka Kapanewon Tempel obtained a correlation of 0.844, which means that the level of relationship between the two variables is classified as very strong because it is in the range of 0.80 - 1.000. Keywords: Parental Social Support and Learning Achievement